1995
DOI: 10.1002/cne.903540404
|View full text |Cite
|
Sign up to set email alerts
|

Projections of the lateral terminal accessory optic nucleus of the common marmoset (Callithrix jacchus)

Abstract: The connections of the lateral terminal nucleus (LTN) of the accessory optic system (AOS) of the marmoset monkey were studied with anterograde 3H-amino acid light autoradiography and horseradish peroxidase retrograde labeling techniques. Results show a first and largest LTN projection to the pretectal and AOS nuclei including the ipsilateral nucleus of the optic tract, dorsal terminal nucleus, and interstitial nucleus of the superior fasciculus (posterior fibers); smaller contralateral projections are to the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
1
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 156 publications
(209 reference statements)
2
25
1
1
Order By: Relevance
“…Thus, whereas a direct AOS-cerebellar connection was described in chinchilla (Winfield et al, 1978) and tree shrew (Haines and Sowa, 1985), none was found in rat, rabbit, cat and marmoset monkey (Kawasaki and Sato, 1980;Feran and Grasse, 1982;Giolli et al, 1984Giolli et al, , 1985aGiolli et al, , 1988bBlanks et al, 1995). This discrepancy may either reflect a real species difference, or result from differences inherent in the techniques used, for instance, anterograde vs. retrograde axonal transport.…”
Section: Precerebellar Projections Of the Aosmentioning
confidence: 80%
See 4 more Smart Citations
“…Thus, whereas a direct AOS-cerebellar connection was described in chinchilla (Winfield et al, 1978) and tree shrew (Haines and Sowa, 1985), none was found in rat, rabbit, cat and marmoset monkey (Kawasaki and Sato, 1980;Feran and Grasse, 1982;Giolli et al, 1984Giolli et al, , 1985aGiolli et al, , 1988bBlanks et al, 1995). This discrepancy may either reflect a real species difference, or result from differences inherent in the techniques used, for instance, anterograde vs. retrograde axonal transport.…”
Section: Precerebellar Projections Of the Aosmentioning
confidence: 80%
“…In monkey, where the MTN is attenuated in size or non-existent, the AOS-inferior olivary projections is shown to arise from neurons of the LTN (Mustari et al, 1994;Blanks et al, 1995). In addition to the rostral dorsal cap, there are also LTN projections to the medial accessory olive in primate .…”
Section: Efferents To the Inferior Olive (Figs 2 4-7)mentioning
confidence: 99%
See 3 more Smart Citations